PB1-F2 Amino Acids Regulate Influenza A Viral Polymerase Activity - Yumi Ueda,; Motoko Tanaka,; Yukihiro Kyan,; Mitsutaka Yoshida,; Kenji Sasahara,; Kyoko Shinya, (Journal of Basic & Applied Sciences, 2014)
In 2001, the 11th influenza A viral protein PB1-F2 was detected and found to be encoded by an alternative open reading frame in the PB1 polymerase gene. PB1-F2 has several unique functions, including roles in promoting apoptosis, increasing inflammation, and regulating viral polymerase activity. This study focused on a single PB1-F2 function: regulation of polymerase activity. We constructed a minigenome system to determine the influence of PB1-F2 amino acid (aa) mutations on polymerase activity. We examined four types of aa mutations: three species-specific aa mutations and one mutation that alters pathogenicity in mice. We discovered that an arginine (R) residue at aa position 29 is highly conserved in avian-derived virus strains. Introducing this mutation into mammalian strain A/WSN/33 (H1N1) led to a marked increase in polymerase activity in mammalian cells.These findings suggest that as PB1-F2 in H5N1 viruses regulates viral polymerase activity, it could be targeted for control of avian influenza infection and drug discovery.